Learning curves among all patients undergoing transcatheter aortic valve implantation in Germany: a retrospective observational study - Kaier, Klaus; Frankenstein, Lutz (International journal of cardiology, 2017)
Background: Transcatheter aortic valve implantation (TAVI) is a rapidly evolving technique for therapy of aortic stenosis. Previous studies report learning curves with respect to in-hospital mortality and clinical complications. We aim to determine whether observed improvements of in-hospital outcomes after TAVI are the result of improvements in procedures or due to a change in the patient population, and whether improvements differ between the transfemoral (TF) and the transapical (TA) approach. Methods: Data was analyzed using risk-adjusted regression analyses in order to track the development of clinical outcomes of all isolated TAVI procedures performed in Germany from 2008 to 2013 (N=32.436) in all German hospitals performing TAVI. Measurements include in-hospital mortality, stroke, bleeding, and mechanical ventilation. Results: Unadjusted mortality rates decrease over time for both TA-TAVI and TF-TAVI. Reductions in mortality were smaller for TA-TAVI than for TF-TAVI. These trends could also be observed for risk-adjusted (standardized) mortality rates, indicating that time trends and differences between TA-TAVI (around 7% in 2013) and TF-TAVI (around 4% in 2013) cannot be explained by changes in the risk factor composition of the patient populations. Bleeding complications decreased for both access routes. Both unadjusted and standardized bleeding rates were substantially higher for TA-TAVI. In addition, TA-TAVI procedures were associated with an increased likelihood of requiring >48h of mechanical ventilation. Conclusions: Observed improvements in TAVI-related in-hospital mortality are not due to a change in patient population. The results indicate the superiority of a TF-first approach.